2010
DOI: 10.1111/j.1365-294x.2010.04677.x
|View full text |Cite
|
Sign up to set email alerts
|

The accumulation of genetic diversity within a canopy‐stored seed bank

Abstract: Many plants regenerate after fire from a canopy-stored seed bank, in which seed are housed in fire resistant confructescences (cones) that remain on maternal plants. This strategy would be favoured if plants accumulate a sufficiently large and genetically diverse seed bank during interfire intervals. We use a 16-year demographic study and surveys of microsatellite variation to quantify and explain the rate of accumulation of genetic diversity within the canopy seed bank of the shrub Banksia spinulosa. Flowerin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
19
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 45 publications
2
19
0
Order By: Relevance
“…These findings support the results of a growing number of studies that have compared genetic diversity across plant life stages (see Honnay et al, 2008 for review), and more specifically, the results of a very limited number of studies that have compared either the soil-or canopystored seedbanks of species occurring in fire-prone habitats (Barrett et al, 2005;Premoli and Kitzberger, 2005;Ayre et al, 2009Ayre et al, , 2010. Our findings likely reflect the presence of long-lived, soil-stored seedbanks that, together with extended inter-fire periods, would allow the build-up of large persistent seedbanks that capture the progeny of a number of years of mating (England et al, 2001), and potentially the contributions of multiple generations of adult plants .…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…These findings support the results of a growing number of studies that have compared genetic diversity across plant life stages (see Honnay et al, 2008 for review), and more specifically, the results of a very limited number of studies that have compared either the soil-or canopystored seedbanks of species occurring in fire-prone habitats (Barrett et al, 2005;Premoli and Kitzberger, 2005;Ayre et al, 2009Ayre et al, , 2010. Our findings likely reflect the presence of long-lived, soil-stored seedbanks that, together with extended inter-fire periods, would allow the build-up of large persistent seedbanks that capture the progeny of a number of years of mating (England et al, 2001), and potentially the contributions of multiple generations of adult plants .…”
Section: Discussionsupporting
confidence: 75%
“…Similar fine-scale spatial structure typically at distances of 5-10 m has been reported for other Proteaceae in fire-prone habitats (Ayre et al, , 2010Forrest et al, 2011;Ritchie and Krauss, 2012;Ayre and O'Brien, 2013) and has been argued to reflect the formation of clusters of closely related seedlings in seed shadows of pre-fire adults. Intriguingly, spatial clustering of seedlings is often reported over large spatial scales than is the case for adults (for example, Ayre et al, 2009).…”
Section: Discussionmentioning
confidence: 61%
“…Similar findings have been reported for the fire-adapted obligate seeder Ulex parviflorus (Moreira et al, 2014). Genetic diversity can be preserved through frequent fires because of adaptations to fire, such as an early age of first flowering and a diverse canopy seed bank due to serotiny (Templeton and Levin, 1979;Ayre et al, 2010), and because of high levels of gene flow Shohami and Nathan, 2014). In the Proteaceae species Banksia hookeriana, for example, genetic diversity in a 9-year-old canopy seed bank accumulated rapidly: the first reproduction event after fire already accounted for >80 % of the genetic diversity detected (based on the Shannon index I) and genetic variation between seed crop years was small (Barrett et al, 2005).…”
Section: Levels Of Genetic Diversity Are Maintained Under High Fire Fsupporting
confidence: 70%
“…Although there were significant correlated matings, the number of pollen parents per seed parent was moderate and the majority of successful pollen came from more distant (>10 m), relatively unrelated sources within populations. High levels of outcrossing have been reported previously in many members of the Proteaceae (Holmes et al 2009;Krauss et al 2009;Ayre et al 2010;Llorens et al 2011). In H. oldfieldii, the correlation of selfing among loci estimates suggested that all the selfing detected was due to biparental mating rather than selfpollination, suggesting there may be a mechanism to prevent self-pollination in this species.…”
Section: Discussionmentioning
confidence: 54%